Chest wall resection and reconstruction for primary and metastatic sarcomas: an 11-year retrospective cohort study. (3rd February 2021) - Prisciandaro, Elena; Hustache-Castaing, Romain; Michot, Audrey; Jougon, Jacques; Thumerel, Matthieu
Abstract:  : OBJECTIVES: Chest wall sarcomas are rare, aggressive malignancies, the management of which mainly revolves around surgery. Radical tumour excision with free margins represents the optimal treatment for loco-regional clinically resectable disease. The objective of this study was to review our 11-year experience with chest wall resection for primary and metastatic sarcomas, focusing on surgical techniques and strategies for reconstruction. METHODS: Retrospective analysis of a comprehensive database of patients who underwent chest wall resection for primary or secondary sarcoma at our Institute from January 2009 to December 2019. RESULTS: Out of 26 patients, 21 (81%) suffered from primary chest wall sarcoma, while 5 (19%) had recurring disease. The median number of resected ribs was 3. Sternal resection was performed in 6 cases (23%). Prosthetic thoracic reconstruction was deemed necessary in 24 cases (92%). Tumour recurrence was observed in 15 patients (58%). The median overall survival was 73.6 months. Primary and secondary tumours showed comparable survival ( P  = 0.49). At univariate analysis, disease recurrence and infiltrated margins on pathological specimens were associated with poorer survival ( P  = 0.014 and 0.022, respectively). In patients with primary sarcoma, the median progression-free survival was 13.3 months. Associated visceral resections were significantly associated to postoperative complications ( P  = 0.02). CONCLUSIONS: Chest wall resection followed by prosthetic reconstruction is feasible in carefully selected patients and should be performed by experienced surgeons with the aim of achieving free resection margins, resulting in improved long-term outcomes.